TAB2 deficiency induces dilated cardiomyopathy by promoting RIPK1-dependent apoptosis and necroptosis - Haifeng Yin; Xiaoyun Guo; Yi Chen; Yachang Zeng; Xiaoliang Mo; Siqi Hong; Hui He; Jing Li; Rachel N. Steinmetz; Qinghang Liu (2022)
Mutations in TGF-β–activated kinase 1 binding protein 2 (TAB2) have been implicated in the pathogenesis of dilated cardiomyopathy and/or congenital heart disease in humans, but the underlying mechanisms are currently unknown. Here, we identified an indispensable role for TAB2 in regulating myocardial homeostasis and remodeling by suppressing receptor-interacting protein kinase 1 (RIPK1) activation and RIPK1-dependent apoptosis and necroptosis. Cardiomyocyte-specific deletion of Tab2 in mice triggered dilated cardiomyopathy with massive apoptotic and necroptotic cell death. Moreover, Tab2-deficient mice were also predisposed to myocardial injury and adverse remodeling after pathological stress. In cardiomyocytes, deletion of TAB2 but not its close homolog TAB3 promoted TNF-α–induced apoptosis and necroptosis, which was rescued by forced activation of TAK1 or inhibition of RIPK1 kinase activity. Mechanistically, TAB2 critically mediates RIPK1 phosphorylation at Ser321 via a TAK1-dependent mechanism, which prevents RIPK1 kinase activation and the formation of RIPK1-FADD-caspase-8 apoptotic complex or RIPK1-RIPK3 necroptotic complex. Strikingly, genetic inactivation of RIPK1 with Ripk1-K45A knockin effectively rescued cardiac remodeling and dysfunction in Tab2-deficient mice. Together, these data demonstrated that TAB2 is a key regulator of myocardial homeostasis and remodeling by suppressing RIPK1-dependent apoptosis and necroptosis. Our results also suggest that targeting RIPK1-mediated cell death signaling may represent a promising therapeutic strategy for TAB2 deficiency–induced dilated cardiomyopathy.